The Influence of Financial Literacy and Disposable Income on the Saving Interest of Street Vendors in Islamic Banks - Ramadhani, Latifa (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2023)
Islamic banks are financial institutions that uphold sharia rules. The Islamic financial framework adheres to the idea of profit sharing. The purpose of this research is to analyze the effect of financial literacy and disposable income on the intention to save traders in Islamic banks. This research is included in the category of quantitative research, using associative methods. Sampling uses the total population because the total population is less than 100 people. The primary data used is the response to the questionnaire distributed to the respondents.. The results of hypothesis testing show that the variables financial literacy and disposable income simultaneously influence the intention to save traders in Islamic banks, with a significant value of 0.025 <0.05. Partially, the financial literacy variable has a significant effect on the intention to save traders in Islamic banks, with a significant value of 0.042 <0.05. Then the variable disposable income has a significant effect on the intention to save traders in Islamic banks, with a significant value of 0.020 <0.05. From the results of the study it can be concluded that financial literacy and disposable income have an influence on the intention to save traders in Islamic banks by 10.9% and 89.1% are influenced by other variables not examined in this study. This of course can contribute to Islamic banks in order to create strategies for customer behavior to be able to attract potential customers, especially street vendors, to save at Islamic banks